Conceptual Study Of Mukhdushika W.S.R. Acne Vulgaris – A Systematic Review - Basantwani, Geeta; Prasad, Rajendra (International Research Journal of Ayurveda & Yoga, 2021)
Generally everyone and particularly youngsters are more conscious for the beauty of their face. Yuvanapidika or Mukhdushika is a condition which disfigures the face. India leads the way in protecting Traditional knowledge and Ayurveda is considered as world’s holistic system. Various studies have been carried out on Acne Vulgaris and Mukhdushika. Ayurvedic regimens along with Yoga’s and Lepa’s are mentioned in various classical Ayurvedic literatures. A systematic review on the concept of Mukhdushika and Acne Vulgaris has been studied through contemporary sciences and modern dermatological references. Various authors and researchers have tried to explore the concept of Mukhdushika (Acne Vulgaris), but this concept needs to be evaluated more. There is much scope for further clinical trials from modern as well as Ayurvedic point of view.